Pembangunan Sistem E-Learning Untuk Kebutuhan TOT (Training Of Trainer) Guru Pada Smk Yp 17-1 Malang Dengan Menggunakan Framework Codeigniter - Niar Ariati; Heru Nurwarsito; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
SMK YP-17-1 Malang is an organization that operates a formal education. It holds a vocational education on a senior-high grade as a continuation from Junior high (SMP, MTS or any comparable junior high). As an organization that holds a formal education, it is imperative for SMK YP 17-1 to implement any govermental policy in its operation. In the process, there will be problems such as difficulties on implementing the dynamically changing curriculum and the problem of developing the staff's proffesionalism. Based on that fact, we need the skill, cooperation, and feedback among teachers on their daily routine so that they can share their knowledge. Hence, need to implemented a software to manage education/training process and also acts as a web-based information gateway for Training of trainers system. The completed system uses CodeIgniter framework that implements Waterfall development cycle and fulfills the functional requirement with 100% validation percentage. All three of the main feature has a complexity level under 21 which proves that this system can be operated with easy maintenance. Moreover, user satisfaction value reaches 84.17% which indicates that the completed system is categorized as